In vivo interactions between Cyc2 and Rus as well as Rus and Cyc1 of Acidithiobacillus ferrooxidans during extracellular oxidization of ferrous iron. (September 2022) - Peng, Zhaofeng; Liu, Ziyu; Jiang, Yongguang; Dong, Yiran; Shi, Liang
Abstract: Acidithiobacillus ferrooxidans oxidizes ferrous iron [Fe(II)] extracellularly for growth, which contributes to formation of acid mine drainage. Critical to its ability to oxidize Fe(II) are the c -type cytochromes Cyc1 and Cyc2 and Cu-containing protein rusticyanin (Rus). To investigate in vivo interactions among these proteins, the cells of A. ferrooxidans grown under Fe(II)-oxidizing condition were crosslinked with formaldehyde, disuccinimidyl suberate (DSS), bis(sulfosuccinimidyl) suberate (BS 3 ) and disuccinimidyl tartrate (DST), separately. The crosslinked cells were then analyzed with the antibodies specific for Cyc1, Rus or Cyc2, respectively. The results showed that formaldehyde, DSS and DST all crosslinked Cyc1 and Rus as well as Rus and Cyc2, but were unable to crosslink Cyc1 and Cyc2. The DSS water-soluble analog BS 3, however, only crosslinked Rus and Cyc2, suggesting near cell surface interaction between Rus and Cyc2. All these results demonstrate for the first time the in vivo interactions between Cyc1 and Rus and between Rus and Cyc2. Based on these results, we propose that after Fe(II) oxidation, Cyc2 transfers the released electrons to the Rus that is inserted inside Cyc2. The Rus inside Cyc2 then transfers electrons across the outer membrane to the Rus in the periplasm where the Rus relays the electrons to Cyc1. Graphical abstract: Image 1 Highlights: Formaldehyde, DSS and DST crosslink Cyc2 & Rus as well as Rus & Cyc1. BS 3 only crosslinks Cyc2 and Rus on the outer membrane. Rus interacts with Cyc2 most likely by inserting itself into Cyc2. Cyc2 & Rus are proposed to transfer electrons across the outer membrane. The periplasmic Rus transfer electrons to the periplasmic Cyc1.